Neck of the World - Rzicznek, F. Daniel (Utah State University, University Libraries, 2007)
May Swenson Poetry Award Volume 11, with foreward by Alice Quinn. Neck of the World is the eleventh volume in the prestigious May Swenson Poetry Award series. In it, Daniel Rzicznek offers poems that, in quick angular language, capture the natural world and at the same time extend it into a surreal vision, sometimes dream-like, sometimes dark. Alice Quinn, judge for the 2007 Swenson Award, says this of Rzicznek's work: ""Throughout, the language pulsates, always vigorous, by turns knotty and crystalline. . . . In Neck of the World, we have a poet with a striking new vision--challenging, rewarding, and bold.